Independence, discipline and employability: study of vocational high school students - Fatwa Tentama; Subardjo Subardjo; Surahma Asti Mulasari (Journal of Education and Learning (EduLearn), 2019)
Many factors can affect employability in Vocational High School students, including independence and disciplinary factors. This study aims to determine the role of independence and discipline towards student employability. As many as 225 students of class XII Vocational High School 1 Kalasan Yogyakarta, Indonesia participated in this study. The sampling technique is cluster random sampling. The research method used is a quantitative method with employability scale, independence scale, and discipline scale as a data collection tool. The data analysis used in this study is multiple linear regression analysis techniques. The findings show that there is a very significant effect between independence and discipline on employability. Partially, there is a very significant influence between independence towards student employability, and there is a very significant influence between discipline on employability. The role of discipline towards employability is more dominant than independence to employability in Vocational High School students.